Hypoxia Exacerbates Negative Emotional State during Inactivity: The Effect of 21 Days Hypoxic Bed Rest and Confinement - Stavrou, Nektarios A. M.; Debevec, Tadej; Eiken, Ola; Mekjavic, Igor B. (Frontiers in Physiology, 2018)
Hypoxia and confinement have both been shown to influence emotional state. It is envisaged that the inhabitants of future planetary habitats will be exposed to concomitant confinement, reduced gravity and hypoxia. We examined the independent and combined effects of a 21-day inactivity/unloading and normobaric hypoxia under confined conditions on various psychological factors. Eleven healthy male participants participated in three 21-day experimental campaigns designed in a cross-over manner: 1) Normobaric hypoxic ambulatory confinement, 2) Normobaric hypoxic bed rest and 3) Normobaric normoxic bed rest. The Profile of Mood States, and the Positive and Negative Affect Schedule were employed to assess the participants’ psychological responses before (Pre), during (Day 7, Day 14 and Day 21) and after (Post) the confinements. The most negative psychological profile appeared on days 14 and 21 of the hypoxic bed rest campaign. A significant increase in depression, tension, and confusion was noted on days 14 and 21 of the hypoxic bed rest condition. Concomitantly, a decrease, albeit not statistically significant, in positive psychological responses was observed. The psychological profile returned to the initial level at Post following all confinements. These data suggest that the combined effect of hypoxia and bed rest induced the most negative effects on an individual’s mood. However, significant intra- and inter-individual differences in psychological responses were noted and should be taken into consideration.